2017
DOI: 10.1364/oe.25.033315
|View full text |Cite
|
Sign up to set email alerts
|

Partial aperture imaging by systems with annular phase coded masks

Abstract: Interferenceless coded aperture correlation holography is a recently developed technique for indirect 3D imaging of objects without two-wave interference. In such systems, the intensity response to a point is first recorded by modulating the light diffracted from a point object by a pseudorandom coded phase mask (CPM). The object intensity response is recorded under identical conditions and with the same CPM by mounting an object at the same axial location as of the point object. The image of the object is rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 28 publications
0
29
0
Order By: Relevance
“…One unique advantage of I-COACH concept implemented by PAIS technique is the ability to image through an annular aperture of diameter D with the similar resolution of a full-disc aperture of the same diameter D. To the best of our knowledge, [61] is the first study which shows that an annular aperture can image general targets without substantial reduction of the image resolution. Annular aperture imaging is a new technology to image objects through part of the aperture area with as close as possible resolution capabilities of the full aperture.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…One unique advantage of I-COACH concept implemented by PAIS technique is the ability to image through an annular aperture of diameter D with the similar resolution of a full-disc aperture of the same diameter D. To the best of our knowledge, [61] is the first study which shows that an annular aperture can image general targets without substantial reduction of the image resolution. Annular aperture imaging is a new technology to image objects through part of the aperture area with as close as possible resolution capabilities of the full aperture.…”
Section: Discussionmentioning
confidence: 99%
“…This statement has practical and theoretical importance. In the practical aspect, the method proposed in [61,72] offers much more efficient imaging in the sense of weight and aperture utilization. In the theoretical aspect, it was demonstrated that reducing the aperture by two orders of magnitude still enables us to transfer the same amount of information transmitted by the original clear aperture.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The object reconstruction is done by correlating the object hologram with a library of point spread holograms (PSHs), where each PSH is recorded for a point object placed at different axial location of the imaging system. I-CAOCH was further developed for extending the system's field of view 22 , for imaging through partial apertures 23 , for better resolving image details 8,24,25 and for seeing through scattering layers 26 . Due to the lack of two wave interference in the I-COACH holography, the optical configurations and calibrations are simpler in comparison to traditional holographic systems.…”
mentioning
confidence: 99%